The Sec61 translocon is a therapeutic vulnerability in multiple myeloma - Antoine Domenger; Caroline Choisy; Ludivine Baron; Véronique Mayau; Emeline Perthame; Ludovic Deriano; Bertrand Arnulf; Jean‐Christophe Bories; Gilles Dadaglio; Caroline Demangel (EMBO Molecular Medicine)
Abstract Multiple myeloma (MM) is an incurable malignancy characterized by the uncontrolled expansion of plasma cells in the bone marrow. While proteasome inhibitors like bortezomib efficiently halt MM progression, drug resistance inevitably develop, and novel therapeutic approaches are needed. Here, we used a recently discovered Sec61 inhibitor, mycolactone, to assess the interest of disrupting MM proteostasis via protein translocation blockade. In human MM cell lines, mycolactone caused rapid defects in secretion of immunoglobulins and expression of pro‐survival interleukin (IL)‐6 receptor and CD40, whose activation stimulates IL‐6 production. Mycolactone also triggered pro‐apoptotic endoplasmic reticulum stress responses synergizing with bortezomib for induction of MM cell death and overriding acquired resistance to the proteasome inhibitor. Notably, the mycolactone–bortezomib combination rapidly killed patient‐derived MM cells ex vivo, but not normal mononuclear cells. In immunodeficient mice engrafted with MM cells, it demonstrated superior therapeutic efficacy over single drug treatments, without inducing toxic side effects. Collectively, these findings establish Sec61 blockers as novel anti‐MM agents and reveal the interest of targeting both the translocon and the proteasome in proteostasis‐addicted tumors.